2020
DOI: 10.48550/arxiv.2007.10727
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficiency of the financial markets during the COVID-19 crisis: time-varying parameters of fractional stable dynamics

Abstract: This paper investigates the impact of COVID-19 on financial markets. It focuses on the evolution of the market efficiency, using two efficiency indicators: the Hurst exponent and the memory parameter of a fractional Lévy-stable motion. The second approach combines, in the same model of dynamic, an alpha-stable distribution and a dependence structure between price returns. We provide a dynamic estimation method for the two efficiency indicators. This method introduces a free parameter, the discount factor, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Recent articles on the financial impact of COVID-19 have reported varying results for different stock markets. For example, it was shown that COVID-19 has been far more destructive to the US stock market than previous infectious diseases [11]; and the entities listed in the US stock market have exhibited a higher reactivity to the recent COVID crisis compared to their Asian and Australian counterparts [12]. However, ref.…”
Section: Introductionmentioning
confidence: 99%
“…Recent articles on the financial impact of COVID-19 have reported varying results for different stock markets. For example, it was shown that COVID-19 has been far more destructive to the US stock market than previous infectious diseases [11]; and the entities listed in the US stock market have exhibited a higher reactivity to the recent COVID crisis compared to their Asian and Australian counterparts [12]. However, ref.…”
Section: Introductionmentioning
confidence: 99%
“…Rapidly evolving coronavirus pandemic brings a devastating effect on the entire world and its economy as a whole [1,2,3,4,5,6,7]. Further instability related to COVID-19 will negatively affect not only on companies and financial markets, but also on traders and investors that have been interested in saving their investment, minimizing risks, and making decisions such as how to manage their resources, how much to consume and save, when to buy or sell stocks, etc., and these decisions depend on the expectation of when to expect next critical change [8,9,10,11,12,13,14,15,16,17,18,19,20,21]. Despite the complexity of the problem, the results of recent studies indicate that significant success has been achieved within the framework of interdisciplinary approaches, and the theory of self-organizationsynergetics [22,23].…”
Section: Introductionmentioning
confidence: 99%